Long noncoding RNA TRPM2-AS acts as a microRNA sponge of miR-612 to promote gastric cancer progression and radioresistance - Xiao, Jian (Oncogenesis, 2020)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of tumorigenesis and are frequently dysregulated in cancers. Here, we identify a critical lncRNA TRPM2-AS which is aberrantly expressed in gastric cancer (GC) tissues by screening The Cancer Genome Atlas Program(TCGA) database of GC cohort, and its upregulation is clinically associated with advanced pathologic stages and poor prognosis in GC patients. Silencing TRPM2-AS inhibits the proliferation, metastasis and radioresistance of GC cell whereas ectopic expression of TRPM2-AS significantly improves the progression of GC cell in multiple experiments. Mechanistically, TRPM2-AS serves as a microRNA sponge or a competitive endogenous RNA (ceRNA) for tumor suppressive microRNA miR-612 and consequently modulates the derepression of IGF2BP1 and FOXM1. Moreover, induced upregulation of IGF2BP1 subsequently increases the expression of c-Myc and promotes GC cell progression. Meanwhile, TRPM2-AS promotes the radioreistance of GC cell through enhancing the expression of FOXM1 as well. Thus, our findings support a new regulatory axis between TRPM2-AS, miR-612, IGF2BP1, or FOXM1 which serve as crucial effectors in GC tumorigenesis and malignant development, suggesting a promising therapeutic and diagnostic direction for GC.